A case of meningitis due to Achromobacter xylosoxidans denitrificans 60 years after a cranial trauma - Manckoundia, Patrick (International Scientific Literature, Inc., 2011)
BACKGROUND: Achromobacter xylosoxidans (AX) is a non-fermentative aerobic Gram-negative bacillus. It is an opportunistic pathogen and the causative agent of various infections. We report an original case of late posttraumatic meningitis due to AX denitrificans. CASE REPORT: An 83-year-old man was hospitalized for acute headache, nausea and vomiting. The emergency brain computer tomography (CT) scan did not reveal any anomaly. In his medical history, there was an auditory injury due to a cranial trauma incurred in a skiing accident 60 years earlier. Cytobiochemical analysis of the cerebrospinal fluid (CSF) revealed increased levels of neutrophils and proteins. The CSF bacterial culture was positive: the Gram stain showed a Gram-negative bacillus, oxidase + and catalase +, and the biochemical pattern using the API 20 NE strip revealed AX dentrificans. Late posttraumatic meningitis on a possible osteomeningeal breach was diagnosed even though the breach was not confirmed because the patient declined a second brain CT scan. The patient was successfully treated with meropenem. CONCLUSIONS: This report demonstrates the importance of searching for unusual or atypical organisms when the clinician encounters meningitis in a particular context, as well as the importance of adequate follow-up of craniofacial traumas.